2015
DOI: 10.1021/acs.est.5b02904
|View full text |Cite
|
Sign up to set email alerts
|

Declining Acidic Deposition Begins Reversal of Forest-Soil Acidification in the Northeastern U.S. and Eastern Canada

Abstract: Decreasing trends in acidic deposition levels over the past several decades have led to partial chemical recovery of surface waters. However, depletion of soil Ca from acidic deposition has slowed surface water recovery and led to the impairment of both aquatic and terrestrial ecosystems. Nevertheless, documentation of acidic deposition effects on soils has been limited, and little is known regarding soil responses to ongoing acidic deposition decreases. In this study, resampling of soils in eastern Canada and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
140
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(152 citation statements)
references
References 56 publications
9
140
3
Order By: Relevance
“…Over the last decades, this region has experienced simultaneous and significant shifts in moisture availability7, increases in atm. CO 2 concentration, and reductions in acid and nitrogen deposition48 (Fig. 1).…”
mentioning
confidence: 97%
“…Over the last decades, this region has experienced simultaneous and significant shifts in moisture availability7, increases in atm. CO 2 concentration, and reductions in acid and nitrogen deposition48 (Fig. 1).…”
mentioning
confidence: 97%
“…For example, stream ANC was negatively correlated with total soil Ca, and stream Ca:Al was negatively correlated with litterfall Ca:Al. These unexpected patterns may be partially due to insufficient sample size (either too few catchments or too few plots within a catchment to capture the full range of variation), seasonally varying patterns of stream/ soil connectivity, or as yet undescribed patterns of stream and soil recovery from acidic deposition (Lawrence et al, 2015). Long-term forest soil sampling efforts in the 1980s and 1990s showed declining exchangeable Ca and increasing soil acidity linked to forest growth and leaching losses (Johnson et al, 1991;Knoepp and Swank, 1995;Lawrence et al, 1995;Likens et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Likens and Buso (2012) suggested that this response was due to changes in the stream ion balance from being historically dominated by Ca(HCO 3 ) 2 , then shifting to CaSO 4 , and currently toward NaHCO 3 . In another study, Lawrence et al (2015) examined soil recovery in 27 sites across the NE USA and eastern Canada by resampling soils after 8-24 years. They found that site specific decline in SO 4 deposition was correlated with increased base saturation and decreased exchangeable Al in the O-horizon.…”
Section: Discussionmentioning
confidence: 99%
“…Additional study units can be selected, but each is statistically analyzed separately to evaluate if soil changes have occurred. Statistical results of multiple study units can then be grouped for the purpose of regional analysis, as demonstrated in Lawrence et al 5 . The type and size of the study unit will depend on the monitoring questions being asked and the following study design considerations.…”
Section: Designing the Soil Monitoring Studymentioning
confidence: 99%
“…By linking multiple resampling studies, responses of forest soils to changes in a major environmental driver were identified over an extensive region (Figure 11). The study of Lawrence et al 5 demonstrated that results of soil resampling studies with differing designs can be aggregated to address broad regional problems. Figure 11).…”
mentioning
confidence: 99%